Screen time and effects on attention deficient hyperactivity disorder in children - A systematic review - Ambarish Ghosh,; Maidul Islam SK,; Raghav Oza, (Asian Journal of Medical Sciences, 2024)
In recent years, screen time exposure and attention-deficit hyperactivity disorder (ADHD) symptom interrelations in children have garnered increasing attention. Understanding the screen time’s impact on ADHD has become crucial due to its potential influence on socialization, neurobehavioral development, and the prevalence of ADHD among pediatric populations. Conforming to the guidelines of the preferred reporting items for systematic reviews and meta-analyses, a systematic examination was undertaken, centering on research investigating the correlation between screen time and ADHD symptoms in children. The search encompassed databases including MEDLINE (through PubMed), ScienceDirect, Wiley online library, PsycINFO, ERIC, JSTOR, and PsycArticles, utilizing descriptors such as “screen time” and “attention-deficit hyperactivity disorder.” The initial search yielded 2480 articles, supplemented by an additional 10 articles from reference searches, resulting in a total of 2480 records. Excluding the duplicates, 1590 articles were screened based on abstracts, of which 130 underwent full-text examination. Ultimately, 15 studies included in this review met the inclusion criteria. These studies, conducted between 2013 and 2023, comprised cross-sectional, longitudinal, and interventional designs, presenting varying associations between screen time and ADHD symptoms across different age groups. The findings from the selected studies depict a complex relationship between screen time exposure and ADHD symptoms in children. While some studies highlight significant correlations between increased screen exposure and ADHD symptoms, others present conflicting results, indicating the need for further research. Understanding these nuances is crucial in formulating targeted interventions and delineating clearer guidelines to manage screen time concerning ADHD in children.